2020
DOI: 10.1007/978-3-030-49161-1_35
|View full text |Cite
|
Sign up to set email alerts
|

Opinion Mining of Consumer Reviews Using Deep Neural Networks with Word-Sentiment Associations

Abstract: Automated opinion mining of consumer reviews is becoming increasingly important due to the rising influence of reviews on online retail shopping. Existing approaches to automated opinion classification rely either on sentiment lexicons or supervised machine learning. Deep neural networks perform this classification task particularly well by utilizing dense document representation in terms of word embeddings. However, this representation model does not consider the sentiment polarity or sentiment intensity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In this regard, Support Vector Machines (SVM) have emerged as a prominent technique in the field of sentiment analysis, both independently [19] and in its advanced [20] and combined forms, such as combining with deep learning [21] and Fuzzy Method [22]. Research has shown that SVM outperforms other methods in sentiment mining tasks.…”
Section: Spam Detectionmentioning
confidence: 99%
“…In this regard, Support Vector Machines (SVM) have emerged as a prominent technique in the field of sentiment analysis, both independently [19] and in its advanced [20] and combined forms, such as combining with deep learning [21] and Fuzzy Method [22]. Research has shown that SVM outperforms other methods in sentiment mining tasks.…”
Section: Spam Detectionmentioning
confidence: 99%
“…A considerable number of tools have been developed for opinion mining to be used in analyzing consumer opinions in most major business environments, such as travelling, accommodation, consumables, materials, products, and services [4]. However, the health sector has witnessed relatively less development.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, such a positive review assists the vendor to gain several biographies by enhancing the productivity and sale of a particular product. 5 Each individual can generously convey their own opinions and reviews without any panic whereas online posing and social media have done this easier to post their opinions and reviews more confidently. Here, both positive and negative opinions are considered as valuable one and this permits the people having nasty thoughts that make it easy for the people to post their opinions and support their product.…”
Section: Introductionmentioning
confidence: 99%